Density functional theory study of the interaction of Cu, Ag, and Au atoms with the regular CeO2 (111) surface - Branda, Maria Marta (2010)
The interaction of Cu, Ag, and Au atoms with the regular terrace sites of the CeO2(111) surface has been investigated within the LDA+U and GGA+U density functional theory approaches using different U values and periodic slab surface models. For the interaction of Cu and Ag with this surface the different methods consistently predict the same qualitative description of stable active sites, the same order of stability and the oxidized character of adsorbed Cu and Ag. For the case of Au the description is more method dependent due to the nearly degeneracy between the solutions between cationic and neutral Au, in agreement with a recent study. The present results are indicative of the strength and limitations of the present density functional theory approaches.